SISTEM PEMERINTAHAN ISLAM MENURUT AL-MAWARDI DAN APLIKASINYA DI INDONESIA - Rahmawati Rahmawati (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2018)
This paper examines the system of Islamic government according to al-Mawardi and its application in Indonesia. The first study focused on the early history of government in the history of Islamic politics since the Prophet built the State of Medina until it developed until the Abbasid dynasty. Al-Mawardi, who lived in the Middle Ages when the political situation at that time was very unstable and led to the decline of the Abbasid dynasty, gave birth to a concept of a government system based on the political reality of his day. Imam al-Mawardi's political thinking was then poured in the work of al-Ahkam al-Sulthaniyyah and became a basic concept for the development of political thought and its application in the modern era including in Indonesia. In Indonesia, the application of al-Mawardi's theory of social contracts explains the relationship between ahl al-halli wal aqdi and ahl Imamah. This concept was then embodied and developed in the system of governance in Indonesia into 3 boards, namely: legislative institutions, executive institutions, and judicial institutions.